Authenticity assessment of spirit vinegar (Part I): Production and analysis methods. - Adéla GRÉGROVÁ; Helena ČÍŽKOVÁ; Jiří MAZÁČ; Michal VOLDŘICH (Kvasný průmysl, 2012)
In recent years, suspicions arose that vinegars may be adulterated by an addition of synthetic acetic acid. Detection of adulteration is based on tracking markers that indicate a failure in compliance with technological processes, reduction of natural components of raw materials or components resulting from vinegar fermentation. Adulterated vinegars may also contain precursors of the production of synthetic products. Application possibilities of chemometric markers are limited; in case of fermented vinegars the determination of the components derived from raw materials can be used, but spirit vinegars are usually very pure. Isotopic analyses, SNIF-NMR and IRMS, seem to be the most reliable tools for the authentication of vinegars.In recent years, suspicions arose that vinegars may be adulterated by an addition of synthetic acetic acid. Detection of adulteration is based on tracking markers that indicate a failure in compliance with technological processes, reduction of natural components of raw materials or components resulting from vinegar fermentation. Adulterated vinegars may also contain precursors of the production of synthetic products. Application possibilities of chemometric markers are limited; in case of fermented vinegars the determination of the components derived from raw materials can be used, but spirit vinegars are usually very pure. Isotopic analyses, SNIF-NMR and IRMS, seem to be the most reliable tools for the authentication of vinegars.